2006
DOI: 10.1111/j.1365-2427.2006.01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating stream bioassessment and landscape ecology as a tool for land use planning

Abstract: 1. Bioassessment has evolved significantly from a method of deciding whether an ecosystem exposed to stressors should 'pass' or 'fail' (or how badly it fails). Society wants some notion of what has caused any observed degradation of ecosystems, and what management strategies might improve degraded ecosystems. Managers also want to predict what negative or positive effects different land use strategies will have on the component ecosystems of a landscape, including lakes and streams. 2. Here we illustrate an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 37 publications
1
26
1
Order By: Relevance
“…We and others Bonada et al, 2006, Bailey et al, 2007 have shown that predictive models and other biological metrics offer countless advantages for evaluating water quality. In the das Velhas River basin, we support the use of benthic assemblages in ecological models for understanding, evaluating, and mapping the environmental condition of hydrographic basins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others Bonada et al, 2006, Bailey et al, 2007 have shown that predictive models and other biological metrics offer countless advantages for evaluating water quality. In the das Velhas River basin, we support the use of benthic assemblages in ecological models for understanding, evaluating, and mapping the environmental condition of hydrographic basins.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, modern tools have been used in biomonitoring programs since the 1970s (Bonada et al, 2006, Bailey et al, 2007. Biomonitoring programs typically compare the ecological conditions of assemblages from test sites against those from reference sites with minimal alterations (Statzner et al, 2001;Bailey et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the factors chosen should assist in the diagnosis of the probable cause of health degradation and inform management actions (Dole麓dec et al, 2006;Bailey et al, 2007). A river system is usually affected by natural and human causes.…”
Section: Causal Factors and Endogenous Variablesmentioning
confidence: 99%
“…The analysis stopped when all the remaining variables had a significant level P < 0.05 (Zar, 1996). The multi-level approach gives realism to the interactions considered by incorporating into the model a typical ''cascade effect'' observed in these processes Bailey et al, 2007). Therefore, in order to simplify the model structure, only the main key-components were introduced as representative ecological indicators, but which obviously could be complemented by other relevant state variables or other dynamic variables in further applications.…”
Section: For Details)mentioning
confidence: 99%
“…Any environmental assessment must begin with a conceptual model that includes the natural geographic and habitat setting, human activity that can potentially stress the ecosystem (e.g., agriculture), stressors resulting from that human activity (e.g., increased nutrients) and the effects of those stressors on the ecosystem (Stevenson et al, 2004). Nowadays environmental assessment is pushed to assist with land use planning decisions and projections of 'what if' scenarios at the landscape scale and, consequently, it is necessary to capture the main cause-effect relationships between human activity and ecosystem responses (Bailey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%